Pengaruh pola makan seimbang terhadap kesehatan tulang pada remaja - 'AINI, AULYA NUR (Maliki Interdisciplinary Journal, 2025)
Nutrition is one of the important factors that affect bone health in adolescents. Diet is a collaboration of a balanced diet and nutritional intake patterns that enter the body. The approach to dietary patterns can be done with various aspects/types of diets. Analysis of dietary pattern studies can complement studies of nutrition and food that affect bone health. This study aims to analyze the effects of a balanced diet on bone health in young people. The research method used is literature research by analyzing various scientific journals and related articles. The results of this study indicate that a balanced diet rich in calcium, vitamin D, protein and other essential nutrients plays an important role in the formation and maintenance of bone density in young people. The implication of this study is the importance of education for a balanced diet for young people and families to prevent bone health problems in old age.